Violência psicológica contra a mulher: uma dominação estruturada pelo simbólico - Navega, Maria Andresa (2023)
Psychological violence is understood as a type of violence against women described in the law as an action or omission that causes or aims to cause damage to a person's self-esteem, identity or development. Without marks on the physical body, it appears through words, gestures, noisy or silent acts that frighten, threaten, humiliate, diminish, and which is sometimes so frequent that it becomes naturalized, almost a way of life. Psychological violence, because it is less tangible, is even more invisible and doubles the silence of women in this situation. It is a type of violence that is very common and still little studied. In this sense, this research sought to investigate the symbolic determinants of psychological violence against women. To do so, we started from a historical-legal contextualization and the articulation with other fields of knowledge to demonstrate how the heteronormative relationship becomes violent, more precisely how the violence named by Brazilian law as "psychological" arises. We also used psychoanalytic theory in Freud and Lacan to explore the transmission of virility and male domination for men and subalternity for women, which was contributed to by reading authors who think about gender and culture. Finally, we discuss the possibilities of ways out of the malaise of violence for women in the social bond and in intimate life.